TRAJECTOIRE HISTORIQUE ET MORPHOLOGIE DES FORCES ARMEES DE LA REPUBLIQUE DEMOCRATIQUE DU CONGO. DE 1960 A 2014 - MUBENGA, Daniel LUKUSA (IJRDO - Journal of Social Science and Humanities Research, 2019)
When independences great movement swept out the African continent at the beginning of 1960, all African states were almost involved in training their armies respectively, as a sign of their national sovereignty. It is in this way that the Democratic Republic of the Congo got its first army the day after its independence, the National Congolese Army which nowadays Armed Forces of the Democratic Republic of Congo after many changes. After sixty years of getting its international sovereignty, once more its armed forces faced many problems and excelled in many weaknesses in terms of function and structure.The analysis depicts the robot portrait of the Armed Forces of the Democratic Republic of the Congo and emphasizes on the historical trajectory and its formation context, its current morphology, including ailments which affected them either on functional or on structural organizational point of view. Furthermore, the analysis raises the question of emergency and necessity of activating the army reform process which has been released since 2002, but it got in lethargy at the elections eve of December 2018 due to bad mood and dissent with their major international partners: UN (United Nations), UE (European union), and the USA (United States of America)